The relationship between positive psychological qualities and prenatal negative emotion in pregnant women: A path analysis - Tuxunjiang, Xiabidan; Wumaier, Gulijianati; Zhang, Wei; Sailike, Bahedana; Wang, Xiaoting; Jiang, Ting (Frontiers in Psychology, 2023)
Objective: Investigating the relationship between positive psychological qualities and negative emotion of pregnant women. Methods: We surveyed 774 pregnant women in a tertiary hospital in Urumqi using the following measures: a self-made general demographic data questionnaire, generalized anxiety disorder-7 scale, patients health questionnaire depression scale-9 item, pregnancy pressure scale, perceived social support scale, general self-efficacy scale, and Connor-Davidson resilience scale. We used the Amos2.03 system to build a structural equation model. Results: For the 774 participants, the scores were as follows: prenatal anxiety, 4.70 ± 3.54; prenatal depression, 6.11 ± 4.14; pregnancy stress, 0.56 ± 0.45; social support, 63.29 ± 14.19; self-efficacy, 26.18 ± 7.25; and psychological resilience, 41.10 ± 22.79. Pregnancy stress was positively impacted anxiety, depression (β = 0.57, 0.30, P < 0.01), and negatively impacted self-efficacy (β = -0.19, P < 0.01). Anxiety was positively impacted depression (β = 0.54, P < 0.01), and negatively impacted social support (β = -0.45, P < 0.01). Social support was positively impacted self-efficacy and resilience (β = 0.37, 0.47, P < 0.01). Resilience was negatively impacted anxiety (β = -0.09, P < 0.01), and self-efficacy was positively impacted resilience (β = 0.41, P < 0.01). Conclusion: Identification of pregnancy stress should be emphasized in pregnant women with negative emotions. Reducing pregnancy stress was an effective way to reduce the risk of anxiety and depression. Efforts to strengthen the positive psychological qualities of pregnant women should focus on cultivating psychological resilience to reduce the occurrence of anxiety, and improving social support should be a priority because it can enhance psychological resilience and self-efficacy.